2021
DOI: 10.1097/bsd.0000000000001222
|View full text |Cite
|
Sign up to set email alerts
|

Protein Supplement and Enhanced Recovery After Posterior Spine Fusion Surgery

Abstract: Objective: The objective of this study was to evaluate the effect of protein supplementation on vertebral fusion and enhanced recovery after posterior spine fusion (PSF) surgery.Summary of Background Data: Nonfusion is one of the most common complications of lumbar spine surgery. It has been shown that protein plays an important role in bone repair; however, its correlation to vertebral fusion following PSF surgery is unknown.Patients and Methods: In this randomized, double-blind clinical trial study, the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…This study found that patients who had perioperative nutritional supplementation had increased cross-sectional areas of their paraspinal muscles, signifying less atrophy than the control group. 26 This group later followed up these results by examining the effects of protein supplementation, as a part of an Enhanced Recovery After Surgery (ERAS) protocol. 26 Patients who underwent posterior spinal fusion and provided with perioperative nutritional supplementation had higher rates of successful vertebral fusions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study found that patients who had perioperative nutritional supplementation had increased cross-sectional areas of their paraspinal muscles, signifying less atrophy than the control group. 26 This group later followed up these results by examining the effects of protein supplementation, as a part of an Enhanced Recovery After Surgery (ERAS) protocol. 26 Patients who underwent posterior spinal fusion and provided with perioperative nutritional supplementation had higher rates of successful vertebral fusions.…”
Section: Discussionmentioning
confidence: 99%
“…26 This group later followed up these results by examining the effects of protein supplementation, as a part of an Enhanced Recovery After Surgery (ERAS) protocol. 26 Patients who underwent posterior spinal fusion and provided with perioperative nutritional supplementation had higher rates of successful vertebral fusions. 26 In addition, they reported that these patients had increases in their levels of tissue-healing mediators, including albumin and alkaline phosphatase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, serum albumin has been shown to enhance osteogenic differentiation and bone formation in bone defect models [ 19 , 20 ]. Khalooeifard et al found that increasing protein intake can improve vertebral fusion rate and enhance the recovery ability of patients after spinal fusion [ 21 ]. There was also a study showing that ALB decreased the risk of non-fusion rate [ 22 ].…”
Section: Introductionmentioning
confidence: 99%